Preliminary studies on electron beam irradiation as a treatment method of radioactive oil sludge - Ana Paula Gimenes Tessaro; Roberto Vicente; Júlio Takehiro Marumo; Antonio Carlos Silva Costa Teixeira; Leandro Goulart de Araujo (Brazilian Journal of Radiation Sciences)
Radiation-induced advanced oxidation processes have been proposed for the treatment of various types of wastes. However, electron beam technologies for the removal of recalcitrant compounds in petroleum wastes are still poorly understood. This work aims at evaluating the effects on the degradation of organic matter from oil sludge by electron beam irradiation. Characterization methods were employed to identify the chemical elements present in the waste. Radiometric analysis was performed to identify radionuclides and measure dose rates. Preliminary immobilization of the untreated waste with cement indicated resistance values very close to the minimum established in national regulation. To treat the waste, an electron beam accelerator, model Dynamitron II, with variable current up to 25 mA was employed and the irradiation doses ranged from 20 to 200 kGy. Solutions were prepared with an initial H2O2 concentration of 1.34 mol·L-1. The effects on the removal of total organic carbon are discussed.